2020
DOI: 10.1039/c9mo00192a
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous humor metabolite profile of pseudoexfoliation glaucoma is distinctive

Abstract: We identified 298 metabolites in pseudoexfoliation (PEX) glaucoma, primary open angle glaucoma (POAG) and non-glaucomatous controls. Machine learning can classify aqueous humor into the three distinct categories and presents the opportunity for future predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 59 publications
0
46
0
Order By: Relevance
“…Eighteen studies were identified on the basis of the inclusion and exclusion criteria. 17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The flow chart for selection of the studies included in this review is shown in Figure 1. All the studies were designed as case-control studies with the sample sizes ranging from 19 to 506.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies were identified on the basis of the inclusion and exclusion criteria. 17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The flow chart for selection of the studies included in this review is shown in Figure 1. All the studies were designed as case-control studies with the sample sizes ranging from 19 to 506.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Among the 18 studies, 13 focused on open-angle glaucoma (OAG), 17,[20][21][22][23][24][25][26][27][28][29][30][31] two treated any glaucoma as cases, 18,35 and the other three investigated primary angle-closure glaucoma (PACG), primary congenital glaucoma (PCG), and pseudoexfoliation glaucoma, respectively. [32][33][34] Among the 13 studies on OAG, four were performed with aqueous humor (AH) samples, [20][21][22][23] three with serum samples, [24][25][26] three with plasma samples, 17,27,28 and the other three with tear samples, 29 occipital brain region, 30 and optic nerve, 31 respectively. Characteristics of the studies are summarized in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…To the best of our knowledge, only one metabolomics study of AH from patients with pseudoexfoliation glaucoma, not XFS, has been conducted thus far (Myer et al, 2020). Similarly to Myer et al (2020), we have found decreased levels of L-arginine.…”
Section: Discussionmentioning
confidence: 50%
“…To the best of our knowledge, only one metabolomics study of AH from patients with pseudoexfoliation glaucoma, not XFS, has been conducted thus far (Myer et al, 2020). Similarly to Myer et al (2020), we have found decreased levels of L-arginine. Interestingly, according to Leruez et al neither arginine nor tryptophan proved to be significant in the plasma of XFS (Leruez et al, 2018), which implies that the metabolism of these amino acids in XFS is affected locally, in the anterior chamber of the eye, rather than systemically.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation